Description of the immature and mature larvae of Bocchus scobiolae Nagy (Hymenoptera: Dryinidae) - Guglielmino, A.; Olmi, M.; Vári, G.; Capradossi, L.; Bückle, C. (Zootaxa, 2022)
The last immature instar and the mature larva of Bocchus scobiolae are described and illustrated for the first time. The affinities of both immature and mature larvae of Bocchus scobiolae and Mystrophorus formicaeformis are discussed to define larval characters of the subfamily Bocchinae.